Extending the Technology Acceptance Model for Electric Vehicle Adoption in Palembang - Subagja, Ghia; Rahmatullah, Reska; Najib, Ahmad Khoirun; Panjaitan, Rahellia (SAFE-Network, 2026)
This study aims to analyzes electric vehicle (EV) adoption in Palembang, Indonesia by extending the Technology Acceptance Model (TAM) with environmental concern and government support. EV adoption is increasingly important as cities seek to reduce transport emissions, but growing urban areas still face practical and behavioral barriers. A quantitative survey of 300 EV users in Palembang was conducted through an online questionnaire capturing daily experience, perceived benefits, ease of use, and views on government support. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings show that perceived usefulness and perceived ease of use have positive and significant effects on EV adoption. Perceived ease of use also has a positive and significant effect on attitude, and attitude further supports adoption. Environmental concern and government support likewise have positive and significant effects, indicating that care for the environment and supportive policies and infrastructure strengthen users’ decisions. Overall, the results suggest that EV adoption is shaped by both technology perceptions and wider policy support. These findings imply that faster EV uptake in Palembang can be supported by improving usability and charging convenience, communicating clear benefits, and expanding incentives, charging facilities, and consistent public information to reduce uncertainty and encourage wider adoption locally.